PEMANFAATAN SOFTWARE IMITOMEASURE UNTUK PENGUKURAN LUAS DAN KELILING PERMUKAAN LUKA AKUT STADIUM II PADA HEWAN UJI MENCIT (Mus musculus) - Alamsjah, Mochammad Amin; Lamid, Mirni; Avianto, Terry Previo (Melek IT : Information Technology Journal, 2023)
Wound is the loss of tissue caused by trauma due to wounds exposed to cuts, collisions, or chemicals, wounds can cause a person to lose productivity during the wound healing process,in addition to good wound care methods to accelerate the wound healing process, it is necessary to have a reliable wound healing monitoring method and not be an additional risk of infection in the wound, imitomeasure software based on the android system can be a safe wound measurement solution and does not provide additional risk of infection in the wound. In the test results by comparing the use of software, verniers and rulers, the results were not significantly different (P>0.05) in the independent sample T test so it can be concluded that the use of imitomeasure software is quite accurate when compared to conventional measurementmethods, besides that this software is very easy and can run on any android and ios-based smartphone so that it can be used by all health personnel.